(untitled) (Estima – Brazilian Journal of Enterostomal Therapy, 2018)
Talking about nursing is talking about many possibilities and opportunities that are present in the daily lives of professionals, because nursing involves knowledge, ethics, responsibility, communication and especially sharing.